CONCEPTUAL FRAMEWORK OF SERVICE INNOVATION FACTORS INFLUENCING TO ORGANIZATIONAL PERFORMANCE OF MUNICIPALITY IN THAILAND - Anake Tunjararuck; Thapong Teerawatananond; Amnuey Saengnoree (My University, 2024)
Introduction: The development of Local Authoritative Organizations (LAO) in Thailand has continued for a long time, amid efforts to centralize power especially since the civil service reform and national political factors in each period have always affected changes in Local Authoritative Organizations (LAO). According to the decentralization plan of the Act on Decentralization Plans and Procedures for Local Administrative Organizations, there are guidelines for transferring missions to local authoritative organizations in 6 areas: 1) infrastructure, 2) quality of life promotion, 3) community organization, society and maintaining peace and order 4) investment, commerce and tourism promotion 5) management and conservation of natural resources and the environment 6) arts and culture, traditions and local wisdom. Currently, there are a total of 7,848 local authoritative organizations, excluding Bangkok Metropolitan and Pattaya City.

Method: To examine the conceptual framework of Service innovation factors influencing to organizational performance of municipality in Thailand.

Results: The findings revealed that Innovative organization and Innovative capability affect to Performance Management through Operational performance and Innovative capability and Service Innovation affects to Organizational Performance

Conclusion: This study concluded that Conceptual framework of Service innovation factors influencing to Organizational performance of Municipality in Thailand consisted of Innovative Organization, Innovative Capability, Service Innovation related to Performance Management and Organizational Performance. Research on Factors in innovation and organizational management that affect the performance of local government organizations in the type of municipality. The researcher created a model by analyzing a total of 5 latent variables, divided into 3 external latent variables: innovative organizations; Innovative capabilities and service innovation As for the internal latent variables, there are 2 variables: performance management and organizational performance, as shown in Figure 6 Conceptual Framework.
Keywords: Conceptual framework; Conceptual model; Service Innovation; Innovation and Knowledge Management